A long-distance inhibitory system regulates haustoria numbers in parasitic plants - Anna Kokla; Martina Leso; Jan Šimura; Cecilia Wärdig; Marina Hayashi; Naoshi Nishii; Yuichiro Tsuchiya; Karin Ljung; Charles W. Melnyk (Proceedings of the National Academy of Sciences, 2025)
The ability of parasitic plants to withdraw nutrients from their hosts depends on the formation of an infective structure known as the haustorium. How parasites regulate their haustoria numbers is poorly understood, and here, we uncovered that existing haustoria in the facultative parasitic plants Phtheirospermum japonicum and Parentucellia viscosa suppressed the formation of new haustoria located on distant roots. Using Phtheirospermum, we found that this effect depended on the formation of mature haustoria and could be induced through the application of external nutrients. To understand the molecular basis of this root plasticity, we analyzed hormone response and found that existing infections upregulated cytokinin-responsive genes first at the haustoria and then more distantly in Phtheirospermum shoots. We observed that infections increased endogenous cytokinin levels in Phtheirospermum roots and shoots, and this increase appeared relevant since local treatments with exogenous cytokinins blocked the formation of both locally and distantly formed haustoria. In addition, local overexpression of a cytokinin-degrading enzyme in Phtheirospermum prevented this systemic interhaustoria repression and increased haustoria numbers locally. We propose that a long-distance signal produced by haustoria negatively regulates future haustoria, and in Phtheirospermum , such a signaling system is mediated by a local increase in cytokinin to regulate haustoria numbers and balance nutrient acquisition.